1979
DOI: 10.1136/bmj.1.6180.1753
|View full text |Cite
|
Sign up to set email alerts
|

Improved glucose control in maturity-onset diabetes treated with high-carbohydrate-modified fat diet.

Abstract: DiscussionOur results indicate that using the foam results in a good topical application of steroid to the lower rectum but that more proximal spread is limited and infrequent. One criticism that could be put forward is that we made no attempt to ensure that the rectum was clear of any hard faecal matter that might prevent the spread of the foam. All the patients, however, had loose stools, and the foam spread no further in them than in the controls.The aim of the study was simply to assess the extent of sprea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
45
1

Year Published

1984
1984
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(51 citation statements)
references
References 16 publications
5
45
1
Order By: Relevance
“…The high-CHO diet has been shown to improve glycemic control (Brunzell et al, 1971;Anderson, 1977;Kiehm et al, 1976;Simpson et al, 1979), lower plasma LDL cholesterol concentrations (O'Dea et al, 1989;Riccardi et al, 1984) and reduce insulin requirements (Anderson, 1977;Kiehm et al, 1976). However, some studies have shown that high-CHO diets have hypoglycemic and hypolipidemic bene®ts only when they contain a large amount of dietary ®bre (O'Dea et al, 1989;Riccardi et al, 1984) and furthermore, other studies have shown that high-CHO diets low in ®bre result in increased plasma glucose and triacylglycerol, and decreased HDL concentrations (Reaven & Olefsky 1974;Brunzell et al, 1974;Ginsberg et al, 1976;Coulston et al, 1983;Sestoft et al, 1985;Coulston et al, 1989) which may persist for more than six weeks (Coulston et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…The high-CHO diet has been shown to improve glycemic control (Brunzell et al, 1971;Anderson, 1977;Kiehm et al, 1976;Simpson et al, 1979), lower plasma LDL cholesterol concentrations (O'Dea et al, 1989;Riccardi et al, 1984) and reduce insulin requirements (Anderson, 1977;Kiehm et al, 1976). However, some studies have shown that high-CHO diets have hypoglycemic and hypolipidemic bene®ts only when they contain a large amount of dietary ®bre (O'Dea et al, 1989;Riccardi et al, 1984) and furthermore, other studies have shown that high-CHO diets low in ®bre result in increased plasma glucose and triacylglycerol, and decreased HDL concentrations (Reaven & Olefsky 1974;Brunzell et al, 1974;Ginsberg et al, 1976;Coulston et al, 1983;Sestoft et al, 1985;Coulston et al, 1989) which may persist for more than six weeks (Coulston et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the large differences in circulating GIP levels, the insulin response to glucose was not affected by the presence of fat. These results suggest that (1) the rate of absorption of carbohydrate is a major determinant of post-prandial metabolic responses even in the presence of fat, (2) fat-stimulated GIP secretion does not potentiate glucose-induced insulin secretion, and (3) the potentiation of the insulin response to glucose when carbohydrate is co-ingested with fat is consistent with the well-documented insulin resistance associated with high fat diets.Key words: Insulin, gastric inhibitory polypeptide, insulin sensitivity, glucose tolerance, diabetes, diet, fat, rate of carbohydrate digestion.Several studies have demonstrated the beneficial effects of high-carbohydrate, high-fibre diets in the treatment of Type 2 (non-insulin-dependent) diabetes [1,2]. The mechanism by which this dietary regimen improves long-term diabetic control remains unclear: is it due to the high complex carbohydrate, high fibre, type of fibre or low fat contents of such diets?…”
mentioning
confidence: 99%
“…Several studies have demonstrated the beneficial effects of high-carbohydrate, high-fibre diets in the treatment of Type 2 (non-insulin-dependent) diabetes [1,2]. The mechanism by which this dietary regimen improves long-term diabetic control remains unclear: is it due to the high complex carbohydrate, high fibre, type of fibre or low fat contents of such diets?…”
mentioning
confidence: 99%
“…Our studies clearly showed improved glycaemic control and reduced total and LDL cholesterol on a diet relatively low in fat and in which readily obtainable fibre-rich foods accounted for the increased intake of carbohydrate (Simpson et al, 1979a;Simpson et al, 1979b;Simpson et al, 1981;Lousley et al, 1984). The improvement was particularly striking when foods rich in soluble fibre were encouraged (Simpson et al, 1981).…”
mentioning
confidence: 50%
“…In fact such observations were not entirely new, similar observations having been made many years earlier by Kempner using his rice diet (Kempner et al, 1958). Inspired by the work of Anderson and also by the studies of Stone and Connor (1963), who drew attention to the potential of the low carbohydrate -high fat diet, then in widespread use, to increase cardiovascular risk, our own group in Oxford, England embarked on a series of carefully controlled studies which helped to further understand the role of dietary fibre (Simpson et al, 1979a;Simpson et al, 1979b;Simpson et al, 1981;Simpson et al, 1982;Lousley et al, 1984;Geekie et al, 1986;Mann, 1984). Each of the studies involved a crossover design in which patients with type 1 and type 2 diabetes were randomised to receive advice regarding the standard diabetic diet of the time, relatively low in carbohydrate and dietary fibre, or an experimental high carbohydrate diet.…”
mentioning
confidence: 62%